Eggshell and Bacterial Cellulose Composite Membrane as Absorbent Material in Active Packaging - S. Ummartyotin; P. Pisitsak; C. Pechyen (International Journal of Polymer Science)
Bacterial cellulose and eggshell composite was successfully developed. Eggshell was mixed with bacterial cellulose suspension and it was casted as a composite film. CaCO3 derived from eggshell was compared with its commercial availability. It can be noted that good dispersion of eggshell particle was prepared. Eggshell particle was irregular in shape with a variation in size. It existed in bacterial cellulose network. Characterization on composite was focused on thermal and mechanical properties. It showed that flexibility and thermal stability of composite were enhanced. No significant effect of mechanical properties was therefore observed. The thermal stability of composite was stable up to 300°C. The adsorption experiment on water and vegetable oil capacity was performed. The enhancement on adsorption was due to the existence of eggshell in bacterial cellulose composite. It exhibited the potential to be a good candidate for absorbent material in active packaging.